Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen pada Wailela Cafe and Resto di Desa Rumah Tiga - Huninhatu, Vifi Dolvina; Papilaya, Josep; Sinay, Francisca Riconita (Jurnal Pendidikan Ekonomi, 2022)
This study aims to determine is to determine and analyze the effect of service quality on consumer satisfaction on Wailela Cafe and Resto products in Rumah Tiga Village. The research approach used is a quantitative research approach. Quantitative research is an attempt by a researcher to find knowledge by providing data in the form of numbers. In this study, the population used is all parts or members of the object to be observed. The population is people, objects, objects, events, or anything that is the object of the survey. The research population is the consumers at Wailela Café Resto. The instrument in this study was a questionnaire, a number of questions given by researchers and respondents, and a scale. Based on a simple linear regression analysis of the results of the regression test (Coefficientsa) H0: 1≤ 0, that is, it has no positive effect on Y, H1: 1 0, that is X has a positive effect on Y. Then the results of the t test for the X1 variable physical evidence obtained the t value -count ₌ 11.818 and Pvalue rate ₌ 0.000. By using a significant limit of 0.05, so the value of sig 0.000 ˂ 0.05 means that the X variable affects the Y variable, meaning that H0 is rejected and H1 is accepted. From the results of this study, it can be proven that the proposed hypothesis is accepted with a significant value of 0.000 ˂ 0.05, it can be concluded that there is an effect of variable X on variable Y or Service Quality has a positive and significant effect on Consumer Satisfaction at Wailela Café And Resto in the Village House Three.